Przestrzeń grozy w powieści Joanny Bator "Ciemno, prawie noc" = The space of terror in Joanna Bator`s novel "Ciemno, prawie noc" - Woźniak, Jesica (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article focuses on the method of world creation featured in Joanna Bator`s novel. Its objective is to explore the ways of creating the mood of terror with especial attention to labyrinth systems in the novel. The article employs selected elements of space theory as well as demonstrates how the language of "Ciemno, prawie noc" contributes to the creation of the mood of terror.
Keywords: powieść grozy; literatura polska; 21 w.